Nominal ISOMERs (Incorrect spellings of medicines eluding researchers)-variants in the spellings of drug names in PubMed: a database review - Ferner, R; Aronson, J (BMJ Publishing Group, 2016)
To examine how misspellings of drug names could impede searches for published literature. Database review. PubMed. The study included 30 drug names that are commonly misspelt on prescription charts in hospitals in Birmingham, UK (test set), and 30 control names randomly chosen from a hospital formulary (control set). The following definitions were used: standard names-the international non-proprietary names, variant names-deviations in spelling from standard names that are not themselves standard names in English language nomenclature, and hidden reference variants-variant spellings that identified publications in textword (tw) searches of PubMed or other databases, and which were not identified by textword searches for the standard names. Variant names were generated from standard names by applying letter substitutions, omissions, additions, transpositions, duplications, deduplications, and combinations of these. Searches were carried out in PubMed (30 June 2016) for "standard name[tw]" and "variant name[tw] NOT standard name[tw]." The 30 standard names of drugs in the test set gave 325 979 hits in total, and 160 hidden reference variants gave 3872 hits (1.17%). The standard names of the control set gave 470 064 hits, and 79 hidden reference variants gave 766 hits (0.16%). Letter substitutions (particularly i to y and vice versa) and omissions together accounted for 2924 (74%) of the variants. Amitriptyline (8530 hits) yielded 18 hidden reference variants (179 (2.1%) hits). Names ending in "in," "ine," or "micin" were commonly misspelt. Failing to search for hidden reference variants of "gentamicin," "amitriptyline," "mirtazapine," and "trazodone" would miss at least 19 systematic reviews. A hidden reference variant related to Christmas, "No-el", was rare; variants of "X-miss" were rarer. When performing searches, researchers should include misspellings of drug names among their search terms.